4CPS-243 Delayed HIV treatment and factors associated. Issue 1 (23rd March 2023) - Casarrubios, GI; Miranda, A; Martínez, E; Dean, C; Codonal, A; Tardáguila, P; Lázaro, A; Delgado, A; Torralba, M
Abstract : Background and Importance: Clinical practice guidelines (EACS, DHHS, Gesida) recommend starting antiretroviral therapy (ART) as soon as possible after HIV diagnosis, irrespective of CD4 cell count (CD4c). Postponing ART start until complementary assessments depends on the setting, medical indications and risk of loss from care. Aim and Objectives: To analyse delay in treatment initiation over the past ten years and to understand factors associated with delayed ART initiation. Material and Methods: Retrospective observational study in patients diagnosed with HIV infection in an integrated health area from January-2012 to June-2022. Variables collected: age, sex, route of infection, healthcare setting of diagnosis, time from diagnosis to ART initiation (delay time), ART, AIDS stage, baseline VL and CD4c. Data were collected from electronic medical records and outpatient dispensation program. Statistical analysis was performed using Student´s t-test and linear regression method (dependent variable: delay time) by SPSS ® v.15.0. Results: 108 patients were included, median age was 34 years (IQR 29.2-42.7) and 76.9% were men. 41.7% were diagnosed in primary care and 58.4% in the hospital setting. 38.9% were in AIDS stage at diagnosis. The predominant route of infection was men who have sex with men (MSM) 50.9%. ART was initiated with nucleoside reverse-transcriptase inhibitors (NRTI) combined with integrase-strand-transfer inhibitors (INSTI) 66.7%, non-nucleoside reverse-transcriptase inhibitors (NNRTI) 13% and boosted protease inhibitors (PI/b) 20.4%. The median baseline logVL was 4.63 (4.13-5.14) and CD4c was 325 (95-500). The median delay was 21 days (IQR 9-55). Factors associated with delay: baseline CD4c (for every 100 CD4 increase the delay time was extended by 2.29 days (95% CI 0.56 to 4.02; p=0.01); baseline logVL (-3.25 days 95% CI 1.57-8.08; p=0.18); AIDS at diagnosis (-5.40 days; 95% CI 3.30-14.10; p=0.2); use of INSTI or PI/b compared to NNRTI (-31.28 days; 95% CI 7.85-54.71; p= 0.016). For each year of evolution, the time to ART initiation was reduced by 3.05 days (95% CI1.59-4.50; p<0.001). Comparing 2012-2018 vs 2019-2022, the delay was reduced by 20 days (95% CI13.66 to 27.26; p<0, 001). Conclusion and Relevance: The delay to ART initiation has been significantly reduced in recent years. Factors related to the decrease in delay are lower CD4c, starting treatment with INSTI or PI/b vs NNRTI and being within 2019-2022 vs 2012-2018. References and/or Acknowledgements: Conflict of Interest: No conflict of interest